Proceedings of the 15th International Workshop on Beryllium Technology (BeWS-15) September, 14-15, 2022, Karlsruhe, Germany - Vladimirov, Pavel; Dorn, Christopher; Gaisin, Ramil (KIT Scientific Reports, 2023)
The 15th International Workshop on Beryllium Technology (BeWS-15) was held as a joint event combining BeWS-15 and industrial forum BeYOND-IX on September 14-15, 2022 in Karlsruhe, Germany with great success as a hybrid event. The workshop was organized by the Karlsruhe Institute of Technology. Participants came from Germany, the US, the UK, Kazakhstan, Latvia, Czech Republic, Japan, Sweden, France and China, totaling 55 persons, which was not expected immediately after the global pandemic.